2014
DOI: 10.3892/mco.2014.433
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of the patella: An uncommon cause of anterior knee pain

Abstract: Abstract. The patella is a rare site for the development of primary tumors. This is the case report of a giant cell tumor (GCT) occurring in the patella in a 25-year-old woman. The patient presented with a 1-year history of occasional right anterior knee pain. The radiological characteristics suggested a benign condition. The intraoperative pathological diagnosis was GCT of the bone. The lesion was treated by radical curettage with adjuvant therapy comprising phenol and ethanol and injection of calcium phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…To exclude metastasis, we evaluated the case with chest x-ray and CT scan. Many authors report that GCT recurrence is high during the initial two years [17-19]. At 24-months of surgery, the patient was free of symptoms; there was no radiological evidence of recurrence or distant metastasis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To exclude metastasis, we evaluated the case with chest x-ray and CT scan. Many authors report that GCT recurrence is high during the initial two years [17-19]. At 24-months of surgery, the patient was free of symptoms; there was no radiological evidence of recurrence or distant metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…GCT lesions are locally aggressive with high chances of recurrence rate. It has been reported that the incidence of metastasis is up to 1%-2% [17-19]. To exclude metastasis, we evaluated the case with chest x-ray and CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…The patella is an unusual location for any primary or secondary bone tumor, and a neoplasm would rarely be considered in the etiology of anterior knee pain. Therefore, the diagnosis of a tumor within this location is delayed in most patients [ 3 ]. Benign lesions are more common and represent 70% of the tumors affecting the patella.…”
Section: Discussionmentioning
confidence: 99%
“…Giant cell tumour of patella shows a well-defined, lytic lesion with no periosteal reaction. 5 On magnetic resonance imaging (MRI), Giant cell tumour of patella shows higher signal intensity on T1-weighted sequences, heterogeneous signal intensity on T2-weighted sequences and fatsuppressed T1-weighted sequences shows a heterogeneously signal intensity lesion. 5 Chondroblastoma of patella shows a well-defined, round or oval lytic lesion and periosteal reaction is absent.…”
Section: Case Reportmentioning
confidence: 99%